Tannin Extract for Sugarcane Juice Clarification - Leite, Inacio Ramos [UNESP]; Barbosa, Roger Darros [UNESP] (Springer, 2021)
Clarification of sugarcane juice is one of the most important steps in the sugar manufacturing process, considering that an efficient clarification may result in highly beneficial effects on the quality and yield of the final product, crystal or refined sugar. Currently, depending on the industrial plant and intended product, the use of calcium hydroxide, phosphoric acid and sulfur dioxide as auxiliary agents for clarification has been consolidated, the latter being questioned for causing adverse health reactions. In this context, the present study evaluated the performance of the natural black Acacia (Acacia mearnsii) tannin extract as an alternative for the sugarcane juice clarification. The results showed that tannin dosages between 300 and 500 ppm along with liming applied at pH 7.3 and 3 ppm of anionic flocculant provided the best performance, resulting in 32-34% of color removal and 89-93% of turbidity removal. Under these conditions, starch and dextran removal increased, 90 and 98%, as compared to 69% and 96%, obtained with conventional treatment. The performance of the tannin also reduced the calcium hardness of clarified juice by up to 18% compared to the conventional treatment, which in turn may prevent fouling in the subsequent steps.
Keywords: Tannin; Black acacia; Clarification; Sugarcane juice